Nodal metabolic tumour volume on baseline 18F‐FDG PET/CT and overall survival in stage II and III NSCLC patients undergoing curative‐intent chemoradiotherapy/radiotherapy. Issue 6 (28th July 2021) - Alipour, Ramin; Bucknell, Nick; Bressel, Mathias; Everitt, Sarah; MacManus, Michael; Siva, Shankar; Hofman, Michael S; Akhurst, Tim; Hicks, Rodney J; Iravani, Amir
Abstract: Introduction: This study aims to investigate whether nodal metabolic tumour volume (nMTV) and nodal total lesion glycolysis (nTLG) on Fluorine‐18 fluoro‐deoxy‐glucose positron emission tomography–computed tomography ( 18 F‐FDG PET/CT) in inoperable node‐positive stage II and III non‐small cell lung cancer (NSCLC) are independent predictors of overall survival (OS) in patients undergoing curative‐intent chemoradiotherapy/radiotherapy (CRT/RT). Methods: Data from two prospective trials between 2004 and 2016 were analysed retrospectively. Primary, nodal and total metabolic tumour volume and total lesion glycolysis (pMTV, nMTV, tMTV, pTLG, nTLG and tTLG, respectively) were derived from baseline 18 F‐FDG PET/CT. Cox regressions were used to model OS by 18 F‐FDG PET/CT parameters adjusting for overall stage. Results: 89 patients with stage II (8%) and stage III (92%) were included. The median age at diagnosis was 67 years; 62% were male. The median follow‐up was 6.9 years; the median OS was 2.2 years (95% CI 1.7–3.1). The median pMTV, nMTV and tMTV were 14 mL (range 0–360), 8 mL (range 0–250) and 34 mL (range 3–384), respectively. In 3 patients, the primary lesion could not be delineated from the central hilar mass. There was no association between nMTV (adjusted HR 1.04, 95% CI 0.95–1.15, P ‐value 0.43), pMTV (adjusted HR 1.0, 95% CI 0.96–1.04, P ‐value 0.92), tMTV (adjusted HR 1.0, 95% CI 0.97–1.04, P ‐value 0.88), nTLG, pTLG or tTLG and OS. Consistent results were noted when patients with central hilar lesions were excluded from analysis. Conclusion: In node‐positive stage II and III NSCLC patients who underwent 18 F‐FDG PET/CT‐guided target delineation curative‐intent concurrent CRT/RT, metabolic parameters did not appear to provide independent prognostication.